The Organology of Rotenese Musical Instruments According to the Hornbostel-Sachs Classification System - Listya, Agastya Rama (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
This article aims to propose a classification of Rotenese traditional musical instruments based on the Hornbostel-Sachs (the H-S) method. The author conducted this ethnographic field research on the island of Rote, East Nusa Tenggara Province, from 2015 to 2016. The seven existing Rotenese traditional musical instruments analyzed in this article are: 1) meko ai or the meko o (the wooden or the bamboo xylophone); 2) the meko besik or the meko lilok (the hanging iron or brass gongs); 3) the meko besik or the meko lilok (the iron or brass metallophone); 4) the labu kici or the labu so’e (the single-headed, bowl-shaped drum); 5) the tambur or the labu (the single-headed, long cylindrical drum); 6) the bitala (the crash cymbals); and 7) the sasandu (the heterochord tube-zither). The only Rotenese traditional musical instrument that is not discussed in this article is kianuk, the two-holed bamboo flute, approximately ten centimeters long. This instrument does not exist anymore. The four aspects discussed in this article are 1) the construction, 2) the materials, 3) the ways of playing, and 4) the size of the instruments. Information was gathered from interviews with some key persons and through photography and video recording. This research acknowledges some limitations; for instance, providing exact information is challenging and limiting in the absence of a standard for meko tuning and making. Therefore, the information given here about the size, the material, the tuning, and the note intervals is an approximation.